(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
In this article, the state of development of research competences of future veterinary specialists in the educational process, the criteria for choosing methods of planning and solving problems of research activities in students, pedagogical-psychological features and stages of research competences in students and their level of development are highlighted. Also, methods of formation of research competences of students in the course of training on the basis of research competences have been revealed.